2010
DOI: 10.1203/pdr.0b013e3181ee4dd2
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Cyclodextrin Administration Normalizes Cholesterol Metabolism in Nearly Every Organ of the Niemann-Pick Type C1 Mouse and Markedly Prolongs Life

Abstract: Niemann-Pick type C1 (NPC1) disease arises from a mutation inactivating NPC1 protein that normally moves unesterified cholesterol from the late endosomal/lysosomal complex of cells to the cytosolic compartment for processing. As a result, cholesterol accumulates in every tissue of the body causing liver, lung, and CNS disease. Treatment of the murine model of this disease, the npc1 Ϫ/Ϫ mouse, s.c. with ␤-cyclodextrin (4000 mg/kg) one time each week normalized cellular cholesterol metabolism in the liver and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
107
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 20 publications
13
107
2
Order By: Relevance
“…The doses of 0-4000 mg/kg HPBCD used in this study were selected based on previous reports. [7][8][9] In addition, the upper dose (20000 mg/kg) of HPBCD does not have any adverse effects in acute toxicity in Npc1 −/− mice, as found in our previous study.…”
Section: Effects Of Hpbcd On Survival In Npc1supporting
confidence: 83%
See 3 more Smart Citations
“…The doses of 0-4000 mg/kg HPBCD used in this study were selected based on previous reports. [7][8][9] In addition, the upper dose (20000 mg/kg) of HPBCD does not have any adverse effects in acute toxicity in Npc1 −/− mice, as found in our previous study.…”
Section: Effects Of Hpbcd On Survival In Npc1supporting
confidence: 83%
“…Previous reports have shown that subcutaneous administration of HPBCD (4000 mg/kg) every week is effective in Npc1 −/− mice. [7][8][9]17) In the current study, we found that subcutaneous injection every week of HPBCD could not maintain serum concentrations for a long time, but survival was clearly improved. However, there are no data on the effects of other frequencies of administration (e.g., every day, twice a week, or continuous infusion) of HPBCD.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…HPβCD is thought to work primarily through cholesterol modulation (Ramirez et al 2010), but it has been shown to complex with other phospholipids and lipids within cells (Zidovetzki and Levitan 2007). Cyclodextrins have been studied in many cellular and organ systems and can affect cellular cholesterol content within hours (Taylor et al 2012), consistent with the timing of injury from ICV injection.…”
Section: Fig 4 Ohc Loss Progressed Over Days For Sq High (A) and Hoursmentioning
confidence: 99%